Procedural Training in Pediatric Emergency Medicine Fellowship: What Are We Teaching and What Do Fellows Need to Learn?. Issue 1 (January 2022) - Weiss, Anna; Myers, Sage; Lockman, Justin L.; Posner, Jill; Shaw, Kathy
Abstract : Background: Life-saving procedures are rarely performed on children in the emergency department, making it difficult for trainees to acquire the skills necessary to provide proficient resuscitative care for children. Studies have demonstrated that residents in general pediatrics and emergency medicine lack exposure to procedures in the pediatric context, but no studies exist regarding procedural training in pediatric emergency medicine (PEM). Although the Accreditation Council for Graduate Medical Education (ACGME) provides a list of procedures in which PEM fellows must be competent, the relevance of this procedure list to actual PEM practice has not been studied. Objectives: This study sought to determine whether PEM fellowships currently provide sufficient exposure to the skills most relevant for practicing PEM physicians. Study Design: Data were collected via anonymous electronic survey from physicians who graduated from PEM fellowship between 2012 and 2016. Survey items measured respondents' comfort with performing critical procedures, and their perceptions of the necessity of knowing how to perform each procedure in their current practice environment. Results: A total of 133 individuals responded to the survey. Respondents unanimously agreed that 18 of the 36 procedures required by the ACGME are necessary to know in their current practice environment. For the remaining 18 mandated procedures, there was significant disagreement among respondents both as to the necessity of the procedure in current practice and respondents' degree of comfort with performing each procedure. Conclusions: Among recent PEM fellowship graduates, there is significant variation in comfort with performing ACGME-mandated procedures. These data highlight important opportunities for curricular enhancement in the procedural training of PEM physicians. Abstract : Supplemental digital content is available in the text.